2020
DOI: 10.3389/fneur.2020.00559
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Alterations in Brain Perfusion, Venous Oxygenation, and Oxygen Metabolic Rate of Mice: A 17-Month Longitudinal MRI Study

Abstract: Background: Characterization of physiological parameters of the aging brain, such as perfusion and brain metabolism, is important for understanding brain function and diseases. Aging studies on human brain have mostly been based on the cross-sectional design, while the few longitudinal studies used relatively short follow-up time compared to the lifespan. Objectives: To determine the longitudinal time courses of cerebral physiological parameters across the adult lifespan in mice. Methods: The present work exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 82 publications
1
29
1
Order By: Relevance
“…The vasoactive effect of isoflurane on physiological parameters 72 may be one potential confounding factor in animal studies like ours. Therefore, a consistent anesthetic regimen, which has been shown to be helpful in mitigating anesthetic effects over different experimental sessions, 32 was used throughout the current study. With this strategy, while the absolute values of physiological parameters may not be directly comparable with the unanesthetized state, comparisons between groups under a consistent anesthetic regimen are expected to be valid.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The vasoactive effect of isoflurane on physiological parameters 72 may be one potential confounding factor in animal studies like ours. Therefore, a consistent anesthetic regimen, which has been shown to be helpful in mitigating anesthetic effects over different experimental sessions, 32 was used throughout the current study. With this strategy, while the absolute values of physiological parameters may not be directly comparable with the unanesthetized state, comparisons between groups under a consistent anesthetic regimen are expected to be valid.…”
Section: Discussionmentioning
confidence: 99%
“…The arterial oxygenation (Y a ) is generally characterized by a narrow dynamic range and is close to unity (assumed to be 0.99) 26,27 . Global venous oxygenation (Y v ) was assessed by a TRUST MRI technique, which was first developed on human scanners, 28,29 and was recently optimized and utilized on animal MRI systems 30–32 . Specifically, an axial time‐of‐flight (TOF) sequence was first performed to visualize the confluence of sagittal sinuses, with the following parameters: TR/TE = 20/2.6 ms, field of view (FOV) = 16 × 16 mm 2 , matrix size = 256 × 256, 35 axial slices, slice thickness = 0.5 mm, and scan duration = 2.2 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the wild-type mice in our study were scanned at ~12 months of age in order to age-match the late stage APP swe /PS1 dE9 animals, whereas most previous 17 O-MRI studies were carried out in ~3 month-old animals [ 11 , 12 ]. In mice, there are conflicting reports of either no change [ 26 , 31 ] or even an increase in CMRO 2 [ 32 ] with age. However, these studies were performed using indirect estimates of CMRO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…In ageing rodents, resting CBF is less frequently quantified. There have been mixed findings between studies of ageing mice: one longitudinal and one crosssectional study have found no effect of age on regional CBF (Maier et al, 2014;Hirschler et al, 2018), while another longitudinal study reported an increase (Wei et al, 2020). Meanwhile, studies in rats have only calculated the relative change of CBF in response to stimuli rather than quantifying resting perfusion rate.…”
Section: Rationalementioning
confidence: 99%